A food product development project with humanitarian character: an exploratory study - Lucca, Gabriela Loewe; Caldas Fonseca, Susana; Moura, Ana Pinto (Frontiers in Sustainable Food Systems, 2024)
Vulnerable livelihood groups, such as the Fulanis in Guinea-Bissau, are affected by the consequences of inequality, as they lack access to healthy food, a healthy environment and adequate primary health care. Coordination between sectors can be key to building resilient food and health systems by integrating and scaling up preventive and emergency nutrition services, especially in the context of malnutrition. In 2021, a cashew-based food product was launched in Portugal in partnership with an NGO and a Portuguese food retailer. This study aims to explore the development and marketing of the product with humanitarian objectives, assessing its impact on the different stakeholders of the project. A mixed methodology was applied, combining the evaluation of consumer behavior, assessed through self-reported electronic questionnaires and in-depth interviews with the actors involved in the project. According to the retailer group stakeholders, a great opportunity for the future lies in developing new products with a humanitarian character. The results show that consumers are indeed interested in buying a product associated with a humanitarian cause, and that the product “100% Cashew Nut Butter” has a favorable consumer acceptance in terms of sensory attributes. The long-term nature of the project and the financial return were cited as strengths by all NGO stakeholders involved, but all stakeholders agreed that innovation was needed to sustain donations. Thus, this may be a cyclical process: businesses can create demand through product development, while management and consumers, in turn, drive demand. These findings can be used to improve the design of future projects that might use this as an example.